Analysis Of The Influence Of Employee Welfare And Social Gap On Loyalty Professional - Zuriani Ritongan Ritongan; Chairul bariah; Nurjannah Nurjannah; Hayanuddin Hayanuddin (Jurnal Mantik, 2022)
PT. XXX is a companyplantations that are managed professionally so that employees who are truly able to work optimally and optimally are needed to increase the company's ability to compete in this globalization era. One of the most important factors is the employee factor. Improving the quality of human resources is inseparable from increasing employee loyalty to the work they do. To support job loyalty, one of the factors is the level of employee welfare. With the existence of employee welfare, it is hoped that job professionalism can be achieved. Based on the description above, the writer feels interested in conducting a thesis research entitled: "The Influence of Employee Welfare and Social Inequality on Job Loyalty at PT. XXX”. The results of this study are the results of the F test indicating that simultaneously the variables of employee welfare and social inequality have a significant effect simultaneously on job loyalty (y). With this it can be concluded that the hypothesis of this study can be proven. From the t-count value for b1, it is greater than t-table so that employee welfare has a significant effect on job loyalty, while for b2, the t-count value is greater than t-table, thus social inequality has a significant effect on job loyalty